O-Linked Glycosylation of the Mucin Domain of the Herpes Simplex Virus Type 1-specific Glycoprotein gC-1 Is Temporally Regulated in a Seed-and-spread Manner - Nordén, Rickard (J Biol Chem, 2015)
The herpes simplex virus type 1 (HSV-1) glycoprotein gC-1, participating in viral receptor interactions and immunity interference, harbors a mucin-like domain with multiple clustered O-linked glycans. Using HSV-1-infected diploid human fibroblasts, an authentic target for HSV-1 infection, and a protein immunoaffinity procedure, we enriched fully glycosylated gC-1 and a series of its biosynthetic intermediates. This fraction was subjected to trypsin digestion and a LC-MS/MS glycoproteomics approach. In parallel, we characterized the expression patterns of the 20 isoforms of human GalNAc transferases responsible for initiation of O-linked glycosylation. The gC-1 O-glycosylation was regulated in an orderly manner initiated by synchronous addition of one GalNAc unit each to Thr-87 and Thr-91 and one GalNAc unit to either Thr-99 or Thr-101, forming a core glycopeptide for subsequent additions of in all 11 GalNAc residues to selected Ser and Thr residues of the Thr-76–Lys-107 stretch of the mucin domain. The expression patterns of GalNAc transferases in the infected cells suggested that initial additions of GalNAc were carried out by initiating GalNAc transferases, in particular GalNAc-T2, whereas subsequent GalNAc additions were carried out by followup transferases, in particular GalNAc-T10. Essentially all of the susceptible Ser or Thr residues had to acquire their GalNAc units before any elongation to longer O-linked glycans of the gC-1-associated GalNAc units was permitted. Because the GalNAc occupancy pattern is of relevance for receptor binding of gC-1, the data provide a model to delineate biosynthetic steps of O-linked glycosylation of the gC-1 mucin domain in HSV-1-infected target cells.